207k views
3 votes
If f(x) = x square - 4x + 6, find f(1) - f(-1)

User Reuscam
by
5.0k points

2 Answers

3 votes

Answer:


The~ value ~of~ f(1) - f(-1)~ is~ -8.

Explanation:


The~given~function:


f(x)=x^2-4x+6


We~ need~ to~ find~ the~ value ~of ~f(1) - f(-1).


Substitute~ x=1~ in~ the~ given~ function.


f(1)=(1)^2-4(1)+6=3


Substitute~ x=-1~ in~ the~ given ~function .


f(-1)=(-1)^2-4(-1)+6=11


The~ of ~f(1) - f(-1)~ is


f(1)-f(-1)=3-11=-8

Therefore, the value of f(1) - f(-1) is -8.

User Deem
by
5.6k points
3 votes

Answer:

- 8

Explanation:

Evaluate f(1) and f(- 1) by substituting x = 1 and x = - 1 into f(x)

Given

f(x) = x² - 4x + 6, then

f(1) = 1² - 4(1) + 6 = 1 - 4 + 6 = 3

f(- 1) = (- 1)² - 4(- 1) + 6 = 1 + 4 + 6 = 11

Thus

f(1) - f(- 1) = 3 - 11 = - 8

User Jirka
by
4.2k points